FACTORS RELATED TO ELDERLY PRESENCE TO ELDERLY POSYANDU IN THE WORKING AREA OF MEURAXA PUSKESMAS, BANDA ACEH CITY - jamnni, teuku; Fajri, T Khairul; zulfa Nugroho, Erlangga Galih; Afdal (Aceh Sanitation Journal, 2022)
Elderly Posyandu is an integrated service post for the elderly at the village/kelurahan level within the working area of ​​each health center. Elderly who are not active in attending health services at the elderly Posyandu, their health conditions cannot be monitored properly and it is feared that they will threaten their lives with various diseases, both infectious and non-infectious, which are harmful to the body. There are only 29% of elderly who are active in attending the elderly at the Posyandu in the Meuraxa Health Center UPTD Working Area in 2021, which is still far from the government's target of 70%. The purpose of this study was to determine the factors associated with the presence of elderly Keposyandu in the working area of ​​the UPTD Puskesmas Meuraxa, Banda Aceh City in 2022. This type of research is descriptive analytic with cross-sectional. The sampling technique in this study was accidental sampling. The sample in this study was 44 elderly aged ≥ 55 years. The research was conducted from March 28 to June 17, 2022. Data was collected by interview using a questionnaire, then statistical tests were carried out with the chi-square test, data were analyzed using SPSS .